MEDIA MANAGEMENT OF STATE MUSIC RECORDING (CASE STUDY MUSIC RECORDING LOKANANTA SURAKARTA) - Muadz, Muadz (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Music recording industry cannot be separated from the role of recorded music company that enliven the market with recorded music products. High public interest toward recorded music has become a major attention drawer for recorded music stakeholders to make a profit. This industry, moreover, is not static, but dynamic. It is closely related to consumer tastes and the development of communication information technology. In other words, we can say that this industry is full of uncertainty. Responding to this situation, recorded music companies should be able to adequately apply the principles and functions of media management. Hence, the recorded music produced can well respond to consumer tastes and meet the development of information and communication technology of the industry. This study aims to determine the management processes and functions of Surakarta Lokananta recorded music media which is owned by the government. Lokananta is operated under 2 (two) different institutions, namely the Ministry of Information (Deppen) and the General Printing Company of Republic of Indonesia (Perum PNRI). These two different institutions employ different processes and management functions which, in turn, give impacts on the recorded music and condition of Lokananta. Those differences lie on the applied governance regulations, processes and management’s functions, quality and quantity of financial, recorded music, technology, and human resources. Keywords: Media Management, Music Recording, Company Resources, State Music Recording Company.